Remote Microphone Technology for Children with Hearing Loss or Auditory Processing Issues - Schafer, Erin C.; Kirby, Benjamin; Miller, Sharon (Seminars in Hearing, 2020)
School classrooms are noisy and reverberant environments, and the poor acoustics can be a barrier to successful learning in children, particularly those with multiple disabilities, auditory processing issues, and hearing loss. A new set of listening challenges have been imposed by the recent global pandemic and subsequent online learning requirements. The goal of this article is to review the impact of poor acoustics on the performance of children with auditory processing issues, mild hearing loss, and unilateral hearing loss. In addition, we will summarize the evidence in support of remote microphone technology by these populations.
Keywords: remote microphone; autism; auditory processing